Statistical Forecasting Of Drug-Drug Interactions Using Medicines’ Physiological Similarity - Mishra, Rajesh; Dwivedi, Manu; Dubey, Anubhav; Nyarko, Richard Owusu; Kumari, Mamta; Tripathi, Ajay Kumar; Srivastava, Ateet (Asian Journal of Pharmaceutical Research and Development, 2025)
Taking several drugs at once is a typical practice that raises the possibility of side effects and drug interactions(DDIs). Ensuring patient safety and the effectiveness of treatment methods relies heavily on the prediction and detection of DDIs. To forecast DDIs from drug structures and/or functions, many computational approaches have been used. A computer technique for DDIs prediction based on drug functional similarity is shown here. We established the model using essential biological components such as transporters, targets, enzymes, and carriers (CTET). It We applied it to 21,189 authorized medications. DDIs were determine. We determined the DDIs by gathering all the CTETs associated with each medication and then constructing the corresponding binary vectors. molarity tests to identify DDIs. Inner product-based similarity measures (IPSMs) produced the best prediction values among the similarity approaches that were considered. Researchers looked at 2,394,766 possible drug-pair interactions in total. The program may predict more than 250,000 DDIs with unknown causes. We conclude that the present technique is a general in silico strategy for DDI identification that is both simple and rapid, and we recommend it. In the future, we want to see this suggested strategy implemented as a realistic methodology for DDI identification using pharmacological functional similarities.